Facebook Discourse Analysis of US President Donald Trump - Tasente, Tanase (Technium Social Sciences Journal, 2021)
SNSs, such as Facebook, focus all their attention more on politician communication than institutional communication (political party, government, parliament, presidency, etc.), which encourages the implementation of communication strategies for personalized campaigns. Thus, most of the times, one can reach the paradox that the image of the politicians is more visible than the image of the party, and the personalized aspects of the strategy of the political actor can even contradict the strategies of the communication structures of the political parties. Personalized communication in social media is also highlighted by the use of tagging, most political leaders using this tool to create image links with other political personalities or civil society (ministers, political groups of the same political party, political activists or even political opponents), seeking so that the original post is reproduced and disseminated by those mentioned, in their social groups, forming conversation communities with users that confirm existing convictions. This study focused on analyzing the Key Performance Indicators (KPIs) that facilitate Social Media Communication of Donald Trump, the President of United States of America (number of fans, types of posts, interactions etc.) and analyzing Donald Trump's Facebook speech and identify the most commonly used expressions in Social Media during the term of President. The monitoring period is 20.01.2017 - 16.08.2019.